Descending necrotizing mediastinitis in a healthy young adult - Ochi N; Wakabayashi T; Urakami A; Yamatsuji T; Ikemoto N; Nagasaki Y; Nakagawa N; Honda Y; Nakanishi H; Yamane H; Monobe Y; Akisada T; et al. (Dove Medical Press, 2018)
Nobuaki Ochi,1 Tokio Wakabayashi,2 Atsushi Urakami,3 Tomoki Yamatsuji,3 Naoto Ikemoto,4 Yasunari Nagasaki,1 Nozomu Nakagawa,1 Yoshihiro Honda,1 Hidekazu Nakanishi,1 Hiromichi Yamane,1 Yasumasa Monobe,5 Takeshi Akisada,2 Hiroshi Katayama,4 Yoshio Naomoto,3 Nagio Takigawa1 1Department of General Internal Medicine 4, Kawasaki Medical School, Okayama, Japan; 2Department of Otolaryngology, Kawasaki Medical School, Okayama, Japan; 3Department of General Surgery, Kawasaki Medical School, Okayama, Japan; 4Department of Anesthesiology and Intensive Care Medicine, Kawasaki Medical School, Okayama, Japan; 5Department of Pathology, Kawasaki Medical School, Okayama, Japan Abstract: A 26-year-old man with right lower mandibular and chest pain, fever, and respiratory distress was urgently transported to our hospital. CT images revealed gas collection and an abscess from the neck to the mediastinum with bilateral pleural effusion. Descending necrotizing mediastinitis (DNM) induced by an odontogenic infection of a right mandibular molar abscess was diagnosed. The cervical and mediastinal areas were drained, extensive debridement was performed, necrotic tissue was excised, and broad-spectrum antibiotics were administered immediately. Prompt diagnosis and intensive care were necessary for managing the DNM, and the patient was discharged with no comorbidities. Keywords: descending necrotizing mediastinitis, odontogenic infection, healthy young adult